2008
DOI: 10.1002/jcp.21609
|View full text |Cite
|
Sign up to set email alerts
|

Phorbol ester‐induced podosomes in normal human bronchial epithelial cells

Abstract: Spreading and migration of the basal cells neighboring a wound is essential for airway epithelial repair. To gain insight into the molecular mechanisms that govern these cellular processes, we asked whether normal human airway epithelial cells can form podosomes, a cellular structure discovered from cancer and mesenchymal cells that controls migration and invasion. Herein, we report that phorbol-12, 13-dibutyrate (PDBu), a protein kinase C activator, induced reorganization of cytoskeletal structure in primary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
40
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 27 publications
(42 citation statements)
references
References 53 publications
2
40
0
Order By: Relevance
“…Ventral podosome-like structures and dorsal circular ruffles were identified with Z-stack scanning confocal microscopy, together with immunostaining of multiple marker proteins (55). In the present study, PDBu-induced podosomes in primary human bronchial epithelial cells identified with Zstack scanning confocal microscopy with cortactin as a marker of podosomes are shown as an example.…”
Section: Resultsmentioning
confidence: 60%
See 4 more Smart Citations
“…Ventral podosome-like structures and dorsal circular ruffles were identified with Z-stack scanning confocal microscopy, together with immunostaining of multiple marker proteins (55). In the present study, PDBu-induced podosomes in primary human bronchial epithelial cells identified with Zstack scanning confocal microscopy with cortactin as a marker of podosomes are shown as an example.…”
Section: Resultsmentioning
confidence: 60%
“…Cells were fixed with 4% paraformaldehyde, permeabilized with 0.1% Triton X-100, blocked with 1% bovine serum albumin (BSA), and stained with the designated antibodies Oregon Green 488 phalloidin (Molecular Probe) and Hoechst dye 33342. After gentle washing, the coverslips were mounted on glass slides with Dako fluorescence mounting medium (Dako, Mississauga, Canada) (51,55).…”
mentioning
confidence: 99%
See 3 more Smart Citations